High-accuracy methodology for the integrative restoration of archaeological teeth by using reverse engineering techniques and rapid prototyping. (August 2022) - Vazzana, Antonino; Higgins, Owen Alexander; Oxilia, Gregorio; Lugli, Federico; Silvestrini, Sara; Nava, Alessia; Bondioli, Luca; Bortolini, Eugenio; Di Domenico, Giovanni; Bernardini, Federico; Tuniz, Claudio; Mancini, Lucia; et al.
Graphical abstract: Highlights: Methodology for the integrative restoration of sampled archaeological teeth; Using computer microtomography, reverse engineering, computer-aided design, and rapid prototyping techniques to fabricate missing parts; 3D printing for cultural heritage preservation, research and exhibition. Abstract: The reconstruction of the original morphology of bones and teeth after sampling for physicochemical (e.g., radiocarbon and uranium series dating, stable isotope analysis, paleohistology, trace element analysis) and biomolecular analyses (e.g., ancient DNA, paleoproteomics) is appropriate in many contexts and compulsory when dealing with fossil human remains. The reconstruction protocols available to date are mostly based on manual re-integration of removed portions and can lead to an imprecise recovery of the original morphology. In this work, to restore the original external morphology of sampled teeth we used computed microtomography (microCT), reverse engineering (RE), computer-aided design (CAD) and rapid prototyping (RP) techniques to fabricate customized missing parts. The protocol was tested by performing the reconstruction of two Upper Palaeolithic human teeth from the archaeological excavations of Roccia San Sebastiano (Mondragone, Caserta, southern Italy) and Riparo I of Grotte Verdi di Pradis (Clauzetto, Pordenone, north-eastern Italy) (RSS2 and Pradis 1, respectively), which were sampled for physicochemical and biomolecular analyses. It involved a composite procedure consisting in: a) the microCT scanning of the original specimens; b) sampling; c) the microCT scanning of the specimens after sampling; d) the reconstruction of the digital 3D surfaces of the specimens before and after sampling; e) the creation of digital models of the missing/sampled portions by subtracting the 3D images of the preserved portions (after the sampling) from the images of the intact specimens (before the sampling) by using reverse engineering techniques; f) the prototyping of the missing/sampled portions to be integrated; g) the painting and application of the prototypes through the use of compatible and reversible adhesives. By following the proposed protocol, in addition to the fabrication of a physical element which is faithful to the original, it was possible to obtain a remarkable correspondence between the contact surfaces of the two portions (the original and the reconstructed one) without having to resort to any manipulation/adaptation of either element.